Adoptive TIL Transfer in the Adjuvant Setting for Melanoma: Long-Term Patient Survival - Amir Khammari; Anne-Chantal Knol; Jean-Michel Nguyen; Céline Bossard; Marc-Guillaume Denis; Marie-Christine Pandolfino; Gaëlle Quéreux; Sylvain Bercegeay; Brigitte Dréno (Journal of Immunology Research)
Two first analyses of our clinical trial on TIL as adjuvant therapy for melanoma were published in 2002 and 2007. We present here an update of the clinical results after a 17-year median followup. In this trial, disease-free patients were randomly assigned to receive either TIL/IL-2 or IL-2. The relapse-free survival (RFS) was the primary objective. Eighty-eight patients were enrolled. A new analysis performed in May 2013 did not show significant changes in RFS or OS duration. However, our first finding on the association between the number of invaded lymph nodes and TIL effectiveness was strengthened. The Cox model adjusted on this interaction showed for the first time a significant treatment effect when considering the overall population, both on the RFS and OS. Patients treated with TIL had a longer RFS (P=0.023) or OS (P=0.020). This study being with a very long followup (17 years), confirmed the association between TIL effectiveness and the number of invaded lymph nodes, indicating that a low tumor burden could be a crucial factor enhancing the curative effect of TIL in possible microscopic residual disease. Moreover, we confirmed that a prolonged survival was associated with the presence of specific TIL and a decrease in Foxp3 expression.